Spontaneity and planning in arts attendance: insights from qualitative interviews and the Audience Finder database. Issue 2 (27th May 2019) - Price, Sarah; Perry, Rachel; Mantell, Oliver; Trinder, James; Pitts, Stephanie
ABSTRACT: Arts managers frequently use customer relationship management systems to identify early and late ticket bookers, but to date there has been no comparable investigation of spontaneity and planning through qualitative academic audience research. This paper combines two radically different datasets to draw new insights into booking patterns of audiences for contemporary arts events. Quantitative data from Audience Finder has been analysed to look for trends in early and late booking amongst audiences for contemporary art forms. Qualitative data has been drawn from the Understanding Audiences for the Contemporary Arts study, which used in-depth individual interviews to investigate the contemporary arts attendance of audience members in four UK cities. Interpretative Phenomenological Analysis was then used to draw out insights about where the purchasing point sits within the longer decision to attend. Following a review of marketing and audience research literature on the decision to attend, we present the findings from each of these analyses, looking at moments where they confirm, supplement, contradict, or say something completely outside the remit of the other dataset. We show how the timescale of the decision to attend is influenced by (1) art form conventions and price, (2) geographical region and availability of the arts, (3) attending arts events with companions, and (4) personal preference for planning or spontaneously choosing activities. We end by suggesting a new three-part model for understanding booking patterns, and considering how these insights might be acted upon by arts organisations.